The Significant Rise In Cybercrime Can Be Attributed To Vulnerabilities In Cybersecurity - Ellanda Purwawijaya; Dinur Syahputra; Aripin Rambe; Junerdi Nababan (Jurnal Minfo Polgan, 2024)
In today's world, our dependence on computers extends to even the most basic daily tasks. As users, we consistently engage with computers for activities such as communication, data sharing, information retrieval, social interactions, and more, all conducted over networks. It is evident that the network connecting various devices globally, including servers, computers, laptops, mobile phones, etc., serves as the fundamental technology facilitating these tasks. However, this interconnected system poses a significant threat in the form of cybercrime. Despite the implementation of cybersecurity measures throughout the network, there exist flaws and obstacles that compromise security, leading to the occurrence of these crimes. One can envision the relationship between cybercrime and cybersecurity as a ratio, with cybercrime holding the higher value. This variable is steadily increasing at a greater rate than cybersecurity, indicating a growing imbalance between the two.